US EPA's TSCA risk assessment approach: a case study of asbestos in automotive brakes. (6th December 2021) - Dodge, David G.; Engel, Anna M.; Prueitt, Robyn L.; Peterson, Michael K.; Goodman, Julie E.
Abstract: The United States Environmental Protection Agency (US EPA) is currently refining its approach for risk assessments conducted under the amended Toxic Substances Control Act (TSCA), largely based on recommendations from the National Academies of Sciences, Engineering, and Medicine (NASEM). We identified several issues with the current TSCA risk assessment approach that were not addressed by NASEM in its recommendations. Here, we demonstrate these issues with a case study of the 'Risk Evaluation for Asbestos, Part 1: Chrysotile Asbestos, ' which US EPA released in December 2020. In this evaluation, US EPA found that occupational and some consumer uses of automotive brakes and clutches that contain asbestos result in unreasonable risks. These risks were calculated from estimated exposures during brake work and an inhalation unit risk (IUR) developed for chrysotile asbestos. We found that US EPA overestimated risk as a result of unrealistic inputs to both the exposure and toxicity components of the risk equation, and because the Agency did not fully consider relevant epidemiology and toxicity evidence in its systematic review. Our evaluation demonstrates areas in which the TSCA risk assessment approach could be improved to result in risk evaluations that are supported by the available scientific evidence.